Overview of dietary patterns and vegetable/fish preferences among autistic children - Ilmi, Ibnu Malkan Bakhrul; Octaria, Yessi Crosita; Majida, Lia Awwalia; Olivia, Monica Viorafanti (Nursing and Health Sciences Journal (NHSJ), 2026)
Global autism prevalence is rising, necessitating specialized dietary management. While gluten-free and casein-free (GFCF) diets, along with Omega-3 and antioxidant-rich foods, are recommended to manage symptoms and support brain development, many children with ASD still face significant nutritional challenges. This study aims to describe dietary patterns and preferences for vegetables and fish among children with autism in the Jabodetabek area. This mixed-methods cross-sectional study involved 112 parents of children with autism, selected via cluster random sampling. Data were collected using Food Frequency Questionnaires (FFQ), 2x24-hour food recalls, and in-depth interviews. White rice, tempeh, chicken, and spinach were the primary food sources consumed. Notably, 97% of children still consumed gluten and casein. While a majority expressed a preference for vegetables (61.6%) and fish (81.25%), driven by daily consumption habits, significant macronutrient deficiencies were identified. Specifically, 76.7% of children had insufficient carbohydrate intake, 60.7% lacked adequate fat, and 46.4% were protein-deficient. Autistic children exhibit substantial macronutrient deficits and low adherence to GFCF diets. These findings highlight a critical need for improved dietary education and nutritional interventions for this population.